Hubungan Motivasi Belajar Siswa Dengan Sikap Pemanfaatan Perpustakaan Sekolah - Nurachmah Nurachmah; Dadang Suyadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2013)
The role of library in education is very important in enhancing the learning motivation of students. A good and complete library will not benefit if not utilized optimally. Should the existence of libraries can serve as a good learning place for students in achieving learning objectives expected.This study aimed to find out the relationship between the learning motivation of students with the attitudes of the utilization of the school library in students Competence Skill building graphics SMKN 26 Jakarta. This research is quantitative research.The research method used was a survey method of research correlational. Research conducted at SMKN 26 Jakarta located on Jalan Balai Pustaka Baru I, Rawamangun, East Jakarta. The time execution of research between December 2012 odd semester academic year 2012-2013.Results of the study that there was no significant relationship between students learning motivation and attitude of the utilization of the school library in students Competence Skill Building Graphics SMKN 26 Jakarta but has a very low correlation. The value of the test results of normality (Chi-square test); testing linearity (simple regression test) as well as testing the relationship (correlation tests); for variables X and Y variables (95% confidence level, dk = n-2) is that loans and 15,11 , invariant; Y = 135,79 + X 0,83; retrieved rxy = 0,189, the direction of the positive correlation with categories is very low; and tcount < ttables, receive H0.